Os sentidos do trabalho: estudo com profissionais de T.I que atuam em projetos na grande São Paulo - Ono, Marcelo (2010)
The purpose of this paper is to identify the meanings of work for the professionals in projects. Studying the meanings of work is to comprehend the working aspects that are valued by the subject. It was chosen for this paper the functional approach based on the precursor study of MOW (1987) and on others studies that followed the same thought. A group of 20 IT professionals, who work in projects, were interviewed. The results of this research showed that work is considered essential for those professionals, but family is still the most important issue in their lives. For the interviewed professionals, working is a way to earn money so they can afford their outgoings. Working in TI projects is seen as a stressful job by the workers, due to their deadlines, rhythm, and the pressure of showing results, still it is an environment that allows the subject to develop a quick learning and avoid routine tasks when compared to traditional companies work. This research identified that the IT career and the project environments have an effect on the meanings of work. Some aspects were considered as main characteristics of a work with a meaning; a job that allows some learning; the subject own identification of their abilities; a proper income; quality of life, respect to their private life, less routine activities; satisfaction in concluding a project; that challenges you and contributes to a better society. The interviewees pointed as a job without any meaning, the one which has routine and that presents no need for the consulting and does not respect other groups or professional categories that identified meanings of work standards. A great contribution to the academic studies about the meanings of work was to recognize that the interviewee professional experience time influences the meaning of work and that the professional circle of life can be considered as a variant condition of the meanings of work.